THE ANALYSIS OF THE MORAL VALUES IN THE NOVEL SENSE AND SENSIBILITY - Suryaningrum, Dyah; Marbun, Rismaya; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The main focus of this research is to find the moral values contained in the novel by doing the analysis. To analyze the novel , descriptive analysis is used in this research. The analysis itself is done after following the steps for describing the things that happened in the novel, such as the conflicts between the characters, the plot twist, etc. After doing the analysis through its theme, plot and characters, this novel contains some moral values which divided into positive and negative moral values. The positive moral values are calmness, responsible, kind and good understanding; the negative moral values are heartlessness, greedy, sly, odd, excessive sensibility, and tricky. Those moral values can be applied in the teaching and learning process, especially in English Education Study Program. There are the implementations of the moral values in this novel for teaching and learning process, specifically for English Education Study Program. Based on the analysis, this novel is recommended as one of the literature subjects’ material and suitable for the students considering to their mental age. Keywords: Sense and Sensibility, Analysis, Moral Values Abstrak: Fokus utama dalam penelitian ini adalah menemukan nilai-nilai moral yang terkandung di dalam novel dengan melakukan analisis. Analisis deskriptif digunakan dalam penelitian ini untuk menganalisa novel. Analisis dilakukan setelah mengikuti langkah-langkah untuk mendeskripsikan hal-hal yang terjadi di dalam novel, seperti konflik antar karakter, alur, dan sebagainya. Setelah menyelesaikan analisis pada tema, alur, dan karakter, novel ini mengandung nilai-nilai moral yang mana dibagi menjadi nilai moral positif dan nilai moral negatif. Nilai moral yang positif adalah bersikap tenang, tanggung jawab, baik hati dan pengertian; nilai moral yang negatif adalah dingin hati, serakah, licik, kikuk, sikap berlebihan dan culas. Semua nilai moral tersebut dapat diterapkan dalam proses belajar mengajar, khususnya untuk Program Studi Pendidikan Bahasa Inggris. Berdasarkan pada analisis, novel ini direkomendasikan sebagai salah satu dari bahan mengajar mata kuliah Sastra dan sesuai bagi mahasiswa menilik dari usia mental para mahasiswa. Kata kunci: Sense and Sensibility, Analisis, Nilai Moral